Understanding and strengthening informal seed markets - Sperling, L.; McGrath, S. (Cambridge University Press, 2010)
Informal markets receive little attention from governments and researchers, despite their centrality to farmers' seed security. This paper documents the importance of informal markets for supplying seed and restocking critical plant genetic resources in normal and stress periods. It analyses farmers' rationales for using such markets and their strategic actions in selecting out seed from grain. Conceptual aids for differentiating among market goods - grain, 'implicit seed' and seed - are presented, including tracing of agro-ecological seed sources, traders' seed management behaviour and seed/grain price patterns. Ethiopian case material gives rare insight into how different scales of traders manage the seed/grain divide. Better understanding of informal markets is an important precursor to strengthening them as such markets have unrealized potential to deliver more and higher quality seed, and a greater range of modern and local varieties. Support for informal seed markets could usefully feature in rural livelihood and social protection programmes, but this will require basic shifts in interventions and further refinements in market analysis.